An Analysis of Vermicomposting in Agriculture (International Journal of Innovative Research in Computer Science & Technology, 2022)
massive amount of solid garbage  generated across world is a serious biological & technical  issue. Vermicomposting might be feasible solution for  ecologically friendly solid waste management. This article  gives a broad overview of potential of vermicomposting  as an environmentally beneficial method. Better results are  obtained by combining composting & vermicomposting  procedures. Furrmore, digestion of organic wastes  improves chance for both microbes & earthworm for transforming organic portion of solid waste under  regulated environmental circumstances, which helps for enhancing vermicomposting procedure. By extrapolation,  main variables that impact vermicomposting process  appear to include feeding, stocking density, pH, C/N ratio,  temperature, & moisture. Furrmore, nutrient-rich compost  produced by vermicomposting might be utilised to  generate biogas. As a result, solid waste management & energy generation may both be accomplished at same time  at no additional expense. Vermiculture is environmentally  friendly because earthworms eat anything biodegradable,  & vermicomposting helps with garbage disposal. refore  use of vermicomposting is expected to be high in future  increasing efficiency of earthworms in agriculture.
Keywords: Bio-oxidatio; Earthworms; Organic Waste; Vermicomposting; Vermiculture